Fentanyl, inc. : how rogue chemists are creating the deadliest wave of the opioid epidemic - Westhoff, Ben (New York : Atlantic Monthly Press, 2019)
"A deeply human story, Fentanyl, Inc. is the first deep-dive investigation of an illicit industry that has created a worldwide epidemic, ravaging communities and overwhelming and confounding government agencies that are challenged to combat it. 'A whole new generation of chemicals is radically changing the recreational drug landscape,' writes Ben Westhoff. 'These are known as Novel Psychoactive Substances (NPS) and they include replacements for known drugs like heroin, cocaine, ecstasy, and marijuana. They are synthetic, made in a laboratory, and are much more potent than traditional drugs'"--
Includes bibliographical references (pages 291-328) and index.
Keywords: Designer drugs; Fentanyl; Opioid abuse -- United States; Drug addiction -- United States; Drug abuse -- Fentanyl; Addictions -- Fentanyl; Designer drugs -- Fentanyl; Drug traffic -- China